Metamaterial inspired wideband on-body antenna design for bio-medical applications. (2023) - Rasool Khan, Umhara; Sheikh, Javaid A.; Bashir, Shahid; Ahmed, Suhaib
Abstract: In this paper, a meta -surface inspired flexible antenna prototype is proposed for bio-medical applications. A 1.5 mm Rogers high frequency laminate with permittivity of 3.3 and loss tangent of 0.002 is used as substrate owing to its flexible nature. The proposed antenna is suitable for on-body applications and as such the performance of the prototype was verified on a multilayer phantom model using HFSS tool. Unique properties of meta -surface make miniaturization of the antenna possible with optimum antenna dimensions of 0.24 λ 0  × 0.15 λ 0  × 0.013 λ 0 . The designed antenna is investigated for on-body applications and thereof it is observed that the radiator radiates in the range of 2.14 GHz − 3.4 GHz resulting in resonance at 2.67 GHz.